The Brief COPE: Measurement invariance and psychometric properties among community and at-risk portuguese parents - Nunes, C. (2021)
Parenting generally brings about high internal and external demands, which can be perceived as stressful when they exceed families’ resources. When faced with such stressors, parents need to deploy several adaptive strategies to successfully overcome these challenges. One of such strategies is coping, an important cognitive and behavioural skill. In this study, we intended to examine the psychometric properties of Carver’s (1997) Brief COPE (Coping Orientation to Problems Experienced), extending its cross-cultural validity among a Portuguese sample of community and at-risk parents. The sample comprised community (n = 153) and at-risk (n = 116) parents who completed the brief COPE, the Family Adaptability and Cohesion Scales and the Parenting Stress Index—Short Form. Confirmatory factor analysis, internal consistency, cross sample invariance, convergent and discriminant validity were analysed. Data from the confirmatory factor analysis revealed that the 14-factor model obtained the best fit. The results provided evidence that the Brief COPE is a psychometrically sound instrument that shows measurement invariance across samples and good reliability. Our findings demonstrated that the Portuguese version of brief COPE is a useful, time-efficient tool for both practitioners and researchers who need to assess coping strategies, a relevant construct in family context.